2021
DOI: 10.3389/fendo.2021.704845
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Perivascular Adipose Tissue and Abdominal Aortic Aneurysms

Abstract: Abdominal aortic aneurysms (AAAs) are typically asymptomatic, and there is a high mortality rate associated with aneurysm rupture. AAA pathogenesis involves extracellular matrix degradation, vascular smooth muscle cell phenotype switching, inflammation, and oxidative stress. There is increasing evidence of excessive adipocyte accumulation in ruptured AAA walls. These excessive numbers of adipocytes in the vascular wall have been closely linked with AAA progression. Perivascular adipose tissue (PVAT), a unique … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 83 publications
(105 reference statements)
0
15
0
Order By: Relevance
“…It is infiltrated by multiple immune cells ( 234 ) and heavily innervated ( 246 , 247 ). In pro-inflammatory environment or under the conditions of lipid overload, adipocytes become activated and produce pro-inflammatory cytokines (including TNF and IL-6) and adipokines (such as leptin) which further facilitate immune and VSMC cell activation ( 234 , 248 250 ). Increased adiposity and lipid deposition is associated with the shift toward white adipocytes and heightened accumulation of pro-inflammatory immune cell types ( 251 ), for example pro-inflammatory adipose macrophages ( 252 ).…”
Section: Role Of Perivascular Adipose Tissue In Aaa Developmentmentioning
confidence: 99%
“…It is infiltrated by multiple immune cells ( 234 ) and heavily innervated ( 246 , 247 ). In pro-inflammatory environment or under the conditions of lipid overload, adipocytes become activated and produce pro-inflammatory cytokines (including TNF and IL-6) and adipokines (such as leptin) which further facilitate immune and VSMC cell activation ( 234 , 248 250 ). Increased adiposity and lipid deposition is associated with the shift toward white adipocytes and heightened accumulation of pro-inflammatory immune cell types ( 251 ), for example pro-inflammatory adipose macrophages ( 252 ).…”
Section: Role Of Perivascular Adipose Tissue In Aaa Developmentmentioning
confidence: 99%
“…During the AAA formation and progression, the three-layered vascular wall of the abdominal aorta gradually expands and weakens ( 4 ). Inflammatory cell infiltration, oxidative stress, vascular smooth muscle cell (VSMC) depletion, and destructive extracellular matrix are the primary pathophysiology mechanism of AAA ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Perivascular adipose tissue (PVAT) is a unique tissue in organism and initially thought to provide mechanical support for the vessel wall, which surrounds most blood vessels including the abdominal aorta ( 5 , 11 ). Multicenter research showed differences in PVAT distribution for patients with AAA.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations